Improved Reactivity of Fly Ash-Slag Geopolymer by the Addition of Silica Fume - N. K. Lee; G. H. An; K. T. Koh; G. S. Ryu (Advances in Materials Science and Engineering)
This study investigates the improved reactivity of a geopolymer based on a combination of fly ash and blast furnace slag (BFS) by the addition of silica fume. The geopolymer was synthesized by activating a mixture of fly ash, BFS, and three different types of silica fume with alkali activator. X-ray diffraction (XRD) and inductively coupled plasma-optical emission spectroscopy (ICP-OES) were utilized to characterize the reaction. The silicate structure was also analyzed by nuclear magnetic resonance (NMR) spectroscopy. From these results, it was found that the replacement of fly ash with the silica fume led to a significant decrease in the Q4(1Al) and an increase in the Q4(2Al), Q4(3Al), and Q4(4Al). The Si/Al ratio of the aluminosilicate gel was relatively constant, ranging from 2.0 to 2.6, while the Si/Al ratio of the C-S-H gel increased with the addition of silica fume. Therefore, some of the Al dissolved from the slag contributed to the formation of aluminosilicate gel, and the remnant slag particles mostly participated in the formation of the C-(A)-S-H gel with a decrease in the Q2(1Al). The increase in the reactivity of slag caused by the addition of silica fume was attributed to the reaction of the Al in the slag with the silica fume.